Being Political : Leadership and Democracy in the Pacific Islands - Corbett, Jack (Political scientist) (Book collections on Project MUSE., 2015)
Drawing on more than 110 interviews and other published sources, including autobiographies and biographies, Being Political provides a collective portrait of the Pacific region's political elite. This is an insider account of political life in the Pacific as seen through the eyes of those who have done the job.